2022
DOI: 10.3389/fbuil.2022.801583
|View full text |Cite
|
Sign up to set email alerts
|

Methodology Maps for Model-Based Sensor-Data Interpretation to Support Civil-Infrastructure Management

Abstract: With increasing urbanization and depleting reserves of raw materials for construction, sustainable management of existing infrastructure will be an important challenge in this century. Structural sensing has the potential to increase knowledge of infrastructure behavior and improve engineering decision making for asset management. Model-based methodologies such as residual minimization (RM), Bayesian model updating (BMU) and error-domain model falsification (EDMF) have been proposed to interpret monitoring dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…As stated by [51], using thresholds for falsification enables EDMF to be robust to correlation assumptions between uncertainties; moreover, EDMF explicitly accounts for model bias based on engineering heuristics. Consequently, EDMF, when compared with traditional Bayesian model updating and residual minimisation, has been shown to provide more accurate identification and prediction when there is significant systematic uncertainty.…”
Section: Femu: Error-domain Model Falsification (Edmf)mentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by [51], using thresholds for falsification enables EDMF to be robust to correlation assumptions between uncertainties; moreover, EDMF explicitly accounts for model bias based on engineering heuristics. Consequently, EDMF, when compared with traditional Bayesian model updating and residual minimisation, has been shown to provide more accurate identification and prediction when there is significant systematic uncertainty.…”
Section: Femu: Error-domain Model Falsification (Edmf)mentioning
confidence: 99%
“…Consequently, EDMF, when compared with traditional Bayesian model updating and residual minimisation, has been shown to provide more accurate identification and prediction when there is significant systematic uncertainty. EDMF has been gaining popularity in recent years, since only between 2015 and 2022, there were nine case studies on bridges, four on buildings, and two on geotechnical excavations reported worldwide [51].…”
Section: Femu: Error-domain Model Falsification (Edmf)mentioning
confidence: 99%
“…SPM can relax conservative assumptions by accurate assessment of structural properties. Hence, by leveraging monitoring information, structural interventions may be avoided, thus significantly reducing the cost and environmental impact of infrastructure management (Pai and Smith, 2022). As sustainability and network resilience are becoming major drivers of decisionmaking, bridge owners are projected to increasingly require the use of data-informed frameworks rather than conservative models for assessments regarding bridge safety.…”
Section: Open Access Edited Bymentioning
confidence: 99%